2D Metal–organic framework derived Co/CoSe2 heterojunctions with interfacial electron redistribution as bifunctional electrocatalysts for urea-assisted rechargeable Zn–air batteries. Issue 10 (31st January 2023) - Li, Huanhuan; Liu, Yanyan; Huang, Lulu; Xin, Jie; Zhang, Tengfei; Liu, Ping; Chen, Long; Guo, Wen; Gu, Tiantian; Wang, Gang
Abstract : Benefiting from the structure and interface engineering, the electrocatalyst of Co/CoSe2 @CNx presents superior ORR/UOR bifunctional performance with high stability and high energy conversion efficiency for urea-assisted rechargeable Zn–air batteries. Abstract : The development of oxygen electrode reactions based on earth-abundant nonprecious materials is critically important for the substantial advancement of rechargeable Zn–air batteries (ZABs). Herein, a superb bifunctional electrocatalyst composed of Co/CoSe2 nanoparticles encapsulated in a nitrogen-doped porous graphitized carbon structure (Co/CoSe2 @CNx) has been successfully synthesized. This interface engineering strategy has proven to effectively tune charge redistribution to expedite the charge transfer while the porous graphitized carbon shells provide an optimized environment for charge and mass transport. Accordingly, the Co/CoSe2 @CNx catalyst presents a narrow potential gap (Δ E = 0.54 V) between the UOR potential at 10 mA cm −2 and the half-wave potential for ORR. Herein, the conceptual urea-assisted rechargeable ZABs with fast kinetics and low oxidation potential is demonstrated to remarkably decrease charging voltage and improve energy conversion efficiency. Further, the outstanding electrochemical performance of Co/CoSe2 @CNx enables long-term rechargeability of urea-assisted ZABs, while improving the energy conversion efficiency by 11.8% compared with conventional ZABs. The implementation of urea-assisted rechargeable ZABs based on Co/CoSe2 @CNx with enhanced energy conversion efficiency can promote the practical applications of the ZAB technology.